Ethical Dimensions of the Covid-19 Pandemic: Some Religious Studies Point of View - Yuli Andriansyah (Millah: Journal of Religious Studies, 2022)
Researchers in the field of religious studies have been actively exploring the moral implications of the pandemic from various angles. They have investigated healthcare ethics, addressing issues such as the allocation of limited resources, vaccination prioritization, and the ethical responsibilities of healthcare workers. These scholars have drawn on religious ideas and values to inform ethical decision-making, emphasizing justice, equity, compassion, and solidarity. Moreover, they have examined the pandemic's impact on social justice, including access to healthcare, economic disparities, and racial and ethnic inequalities in COVID-19 outcomes. Additionally, scholars have examined the moral responsibilities of individuals and communities, exploring the ethics of behaviors like social distancing and mask-wearing, as well as the obligations of religious leaders and institutions. Through their research, religious studies scholars provide insights and frameworks for navigating the ethical challenges presented by the pandemic.